The Neandertals of northeastern Iberia: New remains from the Cova del Gegant (Sitges, Barcelona) - Quam, Rolf (2018)
The present study describes a new juvenile hominin mandible and teeth and a new juvenile humerus from level V of the GP2 gallery of Cova del Gegant (Spain). The mandible (Gegant-5) preserves a portion of the right mandibular corpus from the M1 distally to the socket for the dc mesially, and the age at death is estimated as 4.5-5.0 years. Gegant-5 shows a single mental foramen located under the dm1/dm2 interdental septum, a relatively posterior placement compared with recent hominins of a similar developmental age. The mental foramen in Gegant-5 is also placed within the lower half of the mandibular corpus, as in the previously described late adolescent/adult mandible (Gegant-1) from this same Middle Paleolithic site. The Gegant-5 canine shows pronounced marginal ridges, a distal accessory ridge, and a pronounced distolingual tubercle. The P3 shows a lingually-displaced protoconid cusp tip and a distal accessory ridge. The P4 shows a slightly asymmetrical crown outline, a continuous transverse crest, a mesially placed metaconid cusp tip, a slight distal accessory ridge, and an accessory lingual cusp. The M1 shows a Y5 pattern of cusp contact and a well-developed and deep anterior fovea bounded posteriorly by a continuous midtrigonid crest. Gegant-4 is the distal portion of a left humerus from a juvenile estimated to be between 5 and 7 years old at death. The specimen shows thick cortical bone. Although fragmentary, the constellation of morphological and metric features indicates Neandertal affinities for these specimens. Their spatial proximity at the site and similar ages at death suggest these remains may represent a single individual. The addition of these new specimens brings the total number of Neandertal remains from the Cova del Gegant to five, and this site documents the clearest evidence for Neandertal fossils associated with Middle Paleolithic stone tools in this region of the Iberian Peninsula.